Myeloid cells contribute indirectly to VEGF expression upon hypoxia via activation of Müller cells. (January 2018) - Nürnberg, Christina; Kociok, Norbert; Brockmann, Claudia; Lischke, Timo; Crespo-Garcia, Sergio; Reichhart, Nadine; Wolf, Susanne; Baumgrass, Ria; Eming, Sabine A.; Beer-Hammer, Sandra; Joussen, Antonia M.
Abstract: Anti-VEGF-directed therapies have been a milestone for treating retinal vascular diseases. Depletion of monocyte lineage cells suppresses pathological neovascularization in the oxygen-induced retinopathy mouse model. However, the question whether myeloid-derived VEGF-A expression is responsible for the pathogenesis in oxygen-induced retinopathy remained unknown. We analyzed LysMCre-driven myeloid cell-specific VEGF-A knockout mice as well as mice with complete depletion of circulating macrophages through clodronate-liposome treatment in the oxygen-induced retinopathy model by immunohistochemistry, qPCR, and flow cytometry. Furthermore, we analyzed VEGF-A mRNA expression in MIO-M1 cells alone and in co-culture with BV-2 cells in vitro . The myeloid cell-specific VEGF-A knockout did not change relative retinal VEGF-A mRNA levels, the relative avascular area or macrophage/granulocyte numbers in oxygen-induced retinopathy and under normoxic conditions. We observed an insignificantly attenuated pathology in systemically clodronate-liposome treated knockouts but evident VEGF-A expression in activated Müller cells on immunohistochemically stained sections. MIO-M1 cells had significantly higher expression levels of VEGF-A in co-culture with BV-2 cells compared to cultivating MIO-M1 cells alone. Our data show that myeloid-derived cells contribute to pathological neovascularization in oxygen-induced retinopathy through activation of VEGF-A expression in Müller cells. Highlights: A myeloid cell-specific VEGF-A knockout in mice does not change the VEGF-A mRNA level in the retina. Thus, myeloid-derived cells themselves are not a source of relevant VEGF-A levels in the retina. Müller cells co-cultured with microglia cells have a three to five fold higher expression level of VEGF-A than cultured alone. Activated myeloid-derived cells trigger Müller cell VEGF-A secretion, thus contributing to pathological neovascularization in OIR.